The Power of Verbal Expression Examining Language Function in the Short Film ‘The Darkest Blue' - Kamalina, Laela; Ilmiyah, Fasikhatul; Aulia , Sandina Tasya (ETNOLINGUAL, 2023)
This research aims to examine and describe the language functions employed in the dialogues by the cast of the short film "The Darkest Blue" (2021). The qualitative descriptive method is utilized to analyze the data extracted from the dialogues in the film. The language function theory proposed by Holmes (2011) and Halliday (1992) is employed to analyze and categorize the language functions found in the dialogues of the cast. The identified language functions in this study include emotive, phatic, directive, and instrumental. Notably, the emotive function emerges as the most frequently used in "The Darkest Blue," as it serves to convey the characters' emotions and thoughts. The findings of this study contribute to a deeper understanding of language functions employed in various film genres, particularly in the context of short films. It sheds light on how language functions enrich the portrayal of characters and enhance storytelling in films.